2009
DOI: 10.1103/physreva.79.043631
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of fluctuations in a spinor Bose-Einstein condensate

Abstract: Dynamical instabilities due to spin-mixing collisions in a 87 Rb F = 1 spinor Bose-Einstein condensate are used as an amplifier of quantum spin fluctuations. We demonstrate the spectrum of this amplifier to be tunable, in quantitative agreement with mean-field calculations. We quantify the microscopic spin fluctuations of the initially paramagnetic condensate by applying this amplifier and measuring the resulting macroscopic magnetization. The magnitude of these fluctuations is consistent with predictions of a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
161
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(169 citation statements)
references
References 31 publications
7
161
1
Order By: Relevance
“…The extinction of spin-mixing dynamics at negative q for condensates in the |m F = 0 states was observed previously [23].…”
Section: -2supporting
confidence: 72%
See 1 more Smart Citation
“…The extinction of spin-mixing dynamics at negative q for condensates in the |m F = 0 states was observed previously [23].…”
Section: -2supporting
confidence: 72%
“…In addition, the sample was exposed to a linearly polarized microwave-frequency magnetic field detuned by δ = ±2π × 40 kHz from the |F = 1,m F = 0 to |F = 2,m F = 0 hyperfine transition. The resulting ac Zeeman shift of q μ = −h 2 /4δ was used to tune the total quadratic shift q = q B + q μ by varying the Rabi frequency and by choosing the sign of δ [23,24].…”
Section: Methodsmentioning
confidence: 99%
“…In particular, observation of coherent spin oscillations have confirmed the mean-field pendulum model for small condensates 4,9,10 . Spin evolution has been previously observed from metastable spin states in many experiments 6,8,[13][14][15][16][17] , however, the experiments have not yet demonstrated spin dynamic in agreement with quantum calculations, except in the perturbative, low-depletion limit at very short times (where a Bogoliubov expansion around the mean field can be used) 12,13,17 , or for conditions where the mean-field approach suffices. Here, we are able to observe quantum spin dynamics that agree well with quantum calculations and demonstrate a rich array of non-Gaussian fluctuations.…”
mentioning
confidence: 95%
“…The equilibrium states, domain formation and spin dynamics of spinor condensates have been studied in many experiments [6][7][8][9][10][11][12][13][14][15][16][17] . In particular, observation of coherent spin oscillations have confirmed the mean-field pendulum model for small condensates 4,9,10 .…”
mentioning
confidence: 99%
“…In that case, spin-changing collisions may lead to correlated Einstein-Podolsky-Rosen (EPR) pairs in m = ±1 [17,18], in a * fdeuretz@itp.uni-hannover.de process which closely resembles parametric down-conversion in nonlinear optics [19]. As a result, spinor condensates may act as parametric amplifiers of matter waves [20][21][22], opening interesting perspectives for the creation of nonclassical states of matter based on spinor BECs. Recently we have shown that the interplay between trapping potential, quadratic Zeeman effect (QZE), and spin-changing collisions crucially determines the amplification gain [21] and its sensitivity with respect to quantum spin fluctuations [22].…”
Section: Introductionmentioning
confidence: 99%